An equatorward force acting on large floating ice masses: Polfluchtkraft. Issue 74 (29th August 2017) - Engelhardt, Hermann; Engelhardt, Michael
ABSTRACT: This study reviews the effects of a force acting upon ice shelves and icebergs arising from the oblateness of the Earth's geoid and the displacement between the center of mass and the center of buoyancy for an object floating on water. The force has been introduced earlier as Polfluchtkraft or 'pole-fleeing force' by Alfred Wegener and others in the context of continental drift, but it is here applied to floating ice for the first time. It propels icebergs towards the equator, but also tugs on ice shelves making them more likely to break apart in a warming climate with possible consequences for the entire ice sheet.